(untitled) (Texas Journal of Medical Science, 2025)
This article analyzes cases of using a Foley catheter and dinoprostone for cervical preparation for labor and compares their effectiveness. According to the study results, induction of labor with a Foley catheter was more effective than dinoprostone in accelerating cervical ripening and the onset and duration of labor. In addition, the Foley catheter group had a lower complication rate, and the condition of the mother and child was more stable. These results demonstrate the efficacy, safety, and cost-effectiveness of Foley catheter induction of labor in clinical practice.